ON “THE FABRICK OF THE TONGUE”. LANGUAGE METAPHORS USED TO ADVOCATE DESCRIPTIVISM/PRESCRIPTIVISM IN ENGLISH AND ROMANIAN DICTIONARIES - Maria ȘTEFĂNESCU; Mircea MINICĂ (Studia Universitatis Babeş-Bolyai. Philologia, 2023)
There has been considerable scholarly interest in the relationship between language and national identity. The topic is vast and multi-faceted, but in this paper we are especially interested in the manner in which the perceived interdependence between ‘mother tongue’ and ‘fatherland’ has often prompted policies intended to protect the former, and therefore the latter, of whatever was regarded as harmful influence. In particular, we intend to survey some lexicographical work undertaken in Great Britain and (what is now) Romania between the middle of the 18th century and the beginning of the 20th century in order to compare decisions on prescriptivism or descriptivism in dictionaries, and the reasons behind them. While some background information will be necessary, our main focus will be the language metaphors which lexicographers and other people who brought a contribution to dictionary making resorted to in order to support their arguments in favour of or against prescriptivism/descriptivism.